Exercise-induced extracellular vesicles in reprogramming energy metabolism in cancer - Puurand, Marju; Llorente, Alicia; Linē, Aija; Kaambre, Tuuli (Frontiers in Oncology, 2025)
Cancer is caused by complex interactions between genetic, environmental, and lifestyle factors, making prevention strategies, including exercise, a promising avenue for intervention. Physical activity is associated with reduced cancer incidence and progression and systemic anti-cancer effects, including improved tumor suppression and prolonged survival in preclinical models. Exercise impacts the body’s nutrient balance and stimulates the release of several exercise-induced factors into circulation. The mechanisms of how exercise modulates cancer energy metabolism and the tumor microenvironment through systemic effects mediated, in part, by extracellular vesicles (EVs) are still unknown. By transferring bioactive cargo such as miRNAs, proteins and metabolites, exercise-induced EVs may influence cancer cells by altering glycolysis and oxidative phosphorylation, potentially shifting metabolic plasticity – a hallmark of cancer. This short review explores the roles of EVs in cancer as mediators to reprogram cellular energy metabolism through exchanging information inside the tumor microenvironment, influencing immune cells, fibroblast and distant cells. Considering this knowledge, further functional studies into exercise-induced EVs and cellular energy production pathways could inform more specific exercise interventions to enhance cancer therapy and improve patient outcomes.